Determination of Polycyclic Aromatic Hydrocarbons (PAHs) Transfer from Dried Medicinal Plants in Infusions for Therapeutic Purposes - Mihaela Mirela Bratu; Semaghiul Birghila; Corina Birghila; Diana Andreea Danilov; Valentina Coatu; Elena Ristea; Nicoleta Alexandra Damir (Applied Sciences)
The purpose of this paper is to determine the level of polycyclic aromatic hydrocarbons (PAHs) from medicinal plants and infusions prepared using them, as well as assess the transfer of these contaminants from plants to infusions. The separation of compounds was achieved using microwave extraction for dried plants and liquid–liquid extraction in the case of infusions. The extracts were cleaned using solid-phase extraction, and the compounds were analysed using gas chromatography coupled with mass spectrometry (GC-MS). Exposure to PAHs through tea infusion consumption was evaluated by calculating the estimated daily intake (EDI, ng/kg.bw/day) and Margin of Exposure (MOE). The average total content of PAHs varied from 277.22 ± 12.78 to 2466.46 ± 203.45 µg/kg in dry plants, and the compounds benzo[b]fluoranthene (BbF) and benzo[a]pyrene (BaP) were present in all samples. In the herbal tea infusions, the average total PAH content varied between 612.55 ± 46.12 ng/L and 2292.2 ± 140.24 ng/L. The observation was statistically checked using a two-sample paired test. The analysis revealed that PAHs could be split into those for which the content in the medicinal plants is significantly larger than in the infusions and those for which the difference is not significant. The average transfer rates of ∑16PAHs from plants to infusions varied from 7.25 to 32.86%. The MOE values confirmed that consumer exposure to PAHs via tea infusions is very low and safe for health.